2021
DOI: 10.1183/13993003.04066-2020
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of patients with decreased arterial oxyhaemoglobin saturation on pulmonary arterial hypertension drugs

Abstract: RationaleDrugs approved for the treatment of pulmonary arterial hypertension (PAH) improve long-term outcomes. These drugs have pulmonary vasodilator properties which may potentially cause a decrease in arterial oxyhaemoglobin saturation (SaO2) in some patients.ObjectivesThe present retrospective study of the French PAH Registry aimed to describe clinical characteristics and outcomes of patients showing a ≥3% decrease in SaO2 while treated with PAH drugs.MethodsWe reviewed 719 PAH patients. The exclusion crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Hoeper et al reported that oxygenation was not a prognostic marker for survival among prevalent patients with idiopathic PAH under therapy, which supports our results 19 . Recently, Valentin et al (2021) showed that oxygen desaturation (SaO 2 ) ≥ 3% at the time of the first follow-up after one year in combination with low DLCO was significantly associated with worse prognosis of PAH 20 , matching our results linking low OxyHem and low DLCO with early PVD. In this cohort, male sex did not correlate with survival consistent with results from the literature 6 , 21 , 22 .…”
Section: Discussionsupporting
confidence: 88%
“…Hoeper et al reported that oxygenation was not a prognostic marker for survival among prevalent patients with idiopathic PAH under therapy, which supports our results 19 . Recently, Valentin et al (2021) showed that oxygen desaturation (SaO 2 ) ≥ 3% at the time of the first follow-up after one year in combination with low DLCO was significantly associated with worse prognosis of PAH 20 , matching our results linking low OxyHem and low DLCO with early PVD. In this cohort, male sex did not correlate with survival consistent with results from the literature 6 , 21 , 22 .…”
Section: Discussionsupporting
confidence: 88%
“…449 Moreover, in patients with a cardiopulmonary phenotype, PAH medication may cause a decline in the peripheral oxygen saturation. 452 There is little published experience on the use of prostacyclin analogues or prostacyclin receptor agonists in this patient population. 453 The lack of solid evidence for treating elderly patients with PAH and cardiopulmonary comorbidities makes treatment recommendations challenging, and patients should be counselled accordingly.…”
Section: Continuedmentioning
confidence: 99%
“…Interestingly, in the same study, the improvement of pCO2 after 3 months of PAH targeted therapy was noted, and that was associated with higher survival rate [113]. However, a recent study conducted by Valentin et al revealed that in PAH patients, a ≥3% decrease in arterial oxyhemoglobin saturation (SaO2), noticed after 3 months of treatment with PAH-specific drugs, was associated with worse outcomes [114].…”
Section: Pco2mentioning
confidence: 86%